H2020 opportunities for research and innovation in Production Management and Engineering - Raúl Poler (International Journal of Production Management and Engineering)
Horizon 2020 is the new financial instrument implementing the European Union, a global initiative aimed at securing Europe's competitiveness and creating new growth and jobs in Europe. This new EU programme for research and innovation will run from 2014 to 2020 with a budget over €70 billion. What’s new compared with previous framework programs? Horizon 2020 major goal is helping to bridge the gap between research and the market. Research remains essential but innovation plays now an important role. This market-driven approach include creating public-private partnerships to bring together the resources needed. On the other hand, a two year perspective will be provided in order to allow researchers more time to prepare proposals and more scope to make innovative proposals.